2014
DOI: 10.1007/s00213-014-3794-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anticholinergic challenge on psychopathology and cognition in drug-free patients with schizophrenia and healthy volunteers

Abstract: The anticholinergic intervention caused more pronounced psychopathological and cognitive deteriorating effects in patients suffering from schizophrenia than in healthy volunteers. This could be related to the disrupted cholinergic transmission in schizophrenia. Our findings speak on behalf of the need of a more restrictive use of anticholinergics in psychiatric patients. The age-related attenuation of PANSS score increases in patients could be related to the age-dependent changes in dopamine dynamics and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Consequently, lower M 1 density in the DLPFC may be associated with worse verbal learning and memory performance. These findings are compatible with improvements in verbal learning and memory found under M 1/4 agonism by xanomeline in patients with schizophrenia, and deficits in verbal learning and memory found under antagonism by biperiden, which has a 10 fold higher affinity for the M 1 receptor over the other subtypes, in both healthy controls and psychotic disorders ( Shekhar et al, 2008 ; Veselinović et al, 2015 ). Although 123 I-IDEX in in-vitro studies also shows a relatively high affinity for the M 4 subtype, expression rates of M 4 in the DLPFC of humans are low and preclinical studies showed no changes in 123 I-IDEX binding in the frontal cortex of M 4 knock-out mice, suggesting preferential binding of 123 I-IDEX to M 1 receptors in this brain area ( Bakker et al, 2015 ).…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, lower M 1 density in the DLPFC may be associated with worse verbal learning and memory performance. These findings are compatible with improvements in verbal learning and memory found under M 1/4 agonism by xanomeline in patients with schizophrenia, and deficits in verbal learning and memory found under antagonism by biperiden, which has a 10 fold higher affinity for the M 1 receptor over the other subtypes, in both healthy controls and psychotic disorders ( Shekhar et al, 2008 ; Veselinović et al, 2015 ). Although 123 I-IDEX in in-vitro studies also shows a relatively high affinity for the M 4 subtype, expression rates of M 4 in the DLPFC of humans are low and preclinical studies showed no changes in 123 I-IDEX binding in the frontal cortex of M 4 knock-out mice, suggesting preferential binding of 123 I-IDEX to M 1 receptors in this brain area ( Bakker et al, 2015 ).…”
Section: Discussionsupporting
confidence: 81%
“…However, their usage has often been questioned as they themselves cause a range of side-effects, such as cognitive impairment, tardive dyskinesia, blurred vision, dry mouth, problems with urinary retention, psychosis, addiction, and many more ( 30 32 ). To give an example, Veselinović et al ( 33 ) investigated the effect of the administration of anticholinergics on cognition in untreated patients with schizophrenia and healthy control subjects. Their results showed a marked impairment in both groups, which was however more pronounced in the schizophrenia patients, thus again casting doubt on the suitability of these drugs in the treatment of schizophrenia ( 33 ).…”
Section: Antimuscarinic Drugsmentioning
confidence: 99%
“…To give an example, Veselinović et al ( 33 ) investigated the effect of the administration of anticholinergics on cognition in untreated patients with schizophrenia and healthy control subjects. Their results showed a marked impairment in both groups, which was however more pronounced in the schizophrenia patients, thus again casting doubt on the suitability of these drugs in the treatment of schizophrenia ( 33 ).…”
Section: Antimuscarinic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the higher M 1 selectivity of biperiden, a biperiden challenge model would be more appropriate to use in early phase clinical studies of M 1 specific mAChR agonists. Several studies have investigated biperiden as a cognitive challenge model in healthy young [12][13][14][15][16] , healthy elderly 11 , and schizophrenia patients 10 .…”
Section: Introductionmentioning
confidence: 99%